Academic achievement and metabolic control in adolescents with type 1 diabetes. Issue 1 (2nd January 2018) - Lansing, Amy Hughes; Turner, Sara L.; Osborn, Peter G.; Winnick, Joel B.; Taheri, Kiana; Murray, Mary; Butner, Jonathan; Wiebe, Deborah J.; Berg, Cynthia A.
ABSTRACT: Management of type 1 diabetes in adolescence is a complex task requiring self-control within individual and interpersonal domains. This is similarly requisite for academic achievement. Grade point average (GPA) was examined as a barometer of diabetes management reflective of self-control in a challenging daily context. Adolescents with type 1 diabetes ( n  = 172) completed questionnaires on self-control, self-efficacy, parent/peer relationships, and adherence, while mothers reported GPA. Self-control, self-efficacy, and parent/peer relationships predicted GPA, adherence and HbA1c. GPA predicted HbA1c above and beyond adherence and self-control predictors. GPA may be a valuable indicator of individual and interpersonal self-control processes required for diabetes management.